2015
DOI: 10.1002/anie.201503072
|View full text |Cite
|
Sign up to set email alerts
|

Pushing Up Lithium Storage through Nanostructured Polyazaacene Analogues as Anode

Abstract: According to the evidence from both theoretical calculations and experimental findings, conjugated ladder polymers containing large π-conjugated structure, a high number of nitrogen heteroatoms, and a multiring aromatic system, could be an ideal organic anode candidate for lithium-ion batteries (LIBs). In this report, we demonstrated that the nanostructured polyazaacene analogue poly(1,6-dihydropyrazino[2,3g]quinoxaline-2,3,8-triyl-7-(2H)-ylidene-7,8-dimethylidene) (PQL) shows high performance as anode materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
185
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(193 citation statements)
references
References 52 publications
3
185
0
2
Order By: Relevance
“…In the first cycle, the initial discharge and charge capacitances of 2029 and 934 mA h g −1 were respectively obtained, leading to the low initial Coulombic efficiency of 46%. The low initial Coulombic efficiency can be attributed to irreversible reaction, which is a common phenomenon of anode materials for LIBs and could be mitigated by some prelithiation processes . Figure c shows the rate performance of PTTE‐based LIBs, PTTE can deliver specific capacitance of 973 mA h g −1 at a current density of 100 mA g −1 , which is much higher than that of most reported organic anode materials, such as Li 4 C 8 H 4 O 4 nanosheets (232 mA h g −1 at 24.1 mA g −1 ), CMP from porphyrin with 4‐thiophenephenyl groups (TThPP) (666 mA h g −1 at 200 mA g −1 ), poly(bithiophene)/carbon (PBT/C) composite (650 mA h g −1 at 320 mA g −1 ), PDCzBT (404 mA h g −1 at 100 mA g −1 ) and the ordered polypyrrole film (285 mA h g −1 at 300 mA g −1 ) .…”
Section: Resultsmentioning
confidence: 96%
“…In the first cycle, the initial discharge and charge capacitances of 2029 and 934 mA h g −1 were respectively obtained, leading to the low initial Coulombic efficiency of 46%. The low initial Coulombic efficiency can be attributed to irreversible reaction, which is a common phenomenon of anode materials for LIBs and could be mitigated by some prelithiation processes . Figure c shows the rate performance of PTTE‐based LIBs, PTTE can deliver specific capacitance of 973 mA h g −1 at a current density of 100 mA g −1 , which is much higher than that of most reported organic anode materials, such as Li 4 C 8 H 4 O 4 nanosheets (232 mA h g −1 at 24.1 mA g −1 ), CMP from porphyrin with 4‐thiophenephenyl groups (TThPP) (666 mA h g −1 at 200 mA g −1 ), poly(bithiophene)/carbon (PBT/C) composite (650 mA h g −1 at 320 mA g −1 ), PDCzBT (404 mA h g −1 at 100 mA g −1 ) and the ordered polypyrrole film (285 mA h g −1 at 300 mA g −1 ) .…”
Section: Resultsmentioning
confidence: 96%
“…Wu et al demonstrated that the nanostructured polyazaacene analogue, poly(1,6‐dihydropyrazino[2,3 g ] quinoxaline‐2,3,8‐triyl‐7‐(2 H )‐ylidene‐7,8‐dimethylidene), showed high performance as anode materials in LIBs: high capacity (1750 mAh g −1 , 0.05 C), good rate performance (303 mAh g −1 , 5 C), and excellent cycle life (1000 cycles) . The excellent electrochemical performances are attributed to large p‐conjugated structure and a high number of nitrogen heteroatoms.…”
Section: Aq‐based Polymersmentioning
confidence: 99%
“…This potential, however, has not been fully exploited yet, due to some shortcomings of CPs, most importantly related to their relatively low specific capacitance and cycling stability, as well as their limited redox reversibility. 1720 …”
Section: Introductionmentioning
confidence: 99%